Implementing judicial management systems within an integrated justice information framework: a case study on information systems development in the public sector - Rottman, Joseph W. et al. (2007)
For three decades, federal, state, and local agencies have recognized the potential value of integrated information systems for law enforcement and administration of justice. Despite legislative directives, and efforts from associations of government officials to develop common standards for interchange of information, the realization of a truly integrated justice information system (IJIS) has been an elusive target. We describe an in-depth study of alternative approaches to the development of a judicial management system in a large U.S. city and use the case to illustrate the conflicting forces at play in effecting an efficient, comprehensive, and statewide solution. - Reproduced.
Keywords: Judiciary